2017
DOI: 10.1210/js.2017-00192
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance, Hyperinsulinemia, and Mitochondria Dysfunction in Nonobese Girls With Polycystic Ovarian Syndrome

Abstract: Objective:Obese girls with polycystic ovarian syndrome (PCOS) have decreased insulin sensitivity (IS), muscle mitochondrial dysfunction and increased liver fat, which may contribute to their increased risk for type 2 diabetes. Less is known regarding normal-weight girls with PCOS.Methods:Normal-weight girls with PCOS [n =18, age 15.9 ± 1.8 years, body mass index (BMI) percentile 68 ± 18] and normal-weight controls (NWC; n = 20; age 15.0 ± 2.1 years, BMI percentile 60 ± 21) were studied. Tissue-specific IS was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 51 publications
0
64
1
1
Order By: Relevance
“…One proposed mechanism that could disrupt this balance is through mitochondrial dysfunction, characterized by mitochondrial DNA (mtDNA) depletion. It has been associated with the pathogenesis of PCOS, including hyperglycemia, insulin resistance, hyperandrogenism, and anovulation . mtDNA depletion downregulates adiponectin expression, while it stabilizes CTRP6 mRNA, inhibiting its decay .…”
Section: Discussionmentioning
confidence: 99%
“…One proposed mechanism that could disrupt this balance is through mitochondrial dysfunction, characterized by mitochondrial DNA (mtDNA) depletion. It has been associated with the pathogenesis of PCOS, including hyperglycemia, insulin resistance, hyperandrogenism, and anovulation . mtDNA depletion downregulates adiponectin expression, while it stabilizes CTRP6 mRNA, inhibiting its decay .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it stands to reason that the propagation of these mitochondria from a fertilized egg to a blastocyst and ultimately a live-born offspring should result in abnormal mitochondrial function throughout the body. Recent studies in a rat PCOS model have noted mitochondrial dysfunction in the pancreas (57) and kidney (58), and human studies have now reported altered mitochondrial function in skeletal muscle (59) as well as follicular fluid and cumulus cells of PCOS patients (46).…”
Section: Figurementioning
confidence: 99%
“…Data from youth aged 12 to 21 years recruited from the RESistance to InSulin in Type 1 ANd Type 2 diabetes (RESISTANT) study and the Androgens and Insulin Resistance Study (AIRS) cohorts (studies performed prior to ClinicalTrials.gov identifier requirements) were used for this secondary data analysis. Inclusion criteria were BMI ≥ 95th percentile specific for sex and age for the group with obesity, BMI = 10th to 84th percentile for the normal‐weight participants in the control group, and sedentary status, to minimize impacts of varying physical activity on IS (< 3 hours of regular exercise per week, validated with both a 3‐day activity recall and 7 days of accelerometer use).…”
Section: Methodsmentioning
confidence: 99%
“…Informed consent was obtained from all participants ≥ 18 years of age, and parental consent and participant assent were obtained from all participants < 18 years of age. The two groups included in this secondary analysis were originally enrolled as the normal‐weight control group to match those with type 1 diabetes and lean PCOS participants and the control group with obesity to match those with PCOS and T2D participants with obesity. The comparison of the two different weight control groups has not been performed.…”
Section: Methodsmentioning
confidence: 99%